A comparison of epidural analgesia provided by Bupivacaine plus Pethidine, Bupivacaine plus Morphine, or Bupivacaine plus Morphine plus Midazolam for lower limb orthopaedic surgery - Sharma, Nil Raj; Timalsena, Pradip; DC, Sundip (Journal of Kathmandu Medical College, 2014)
Background: Epidural anaesthesia and analgesia in orthopaedic surgeries helps to prevent thromboembolic phenomenon by increasing venodynamics. Adequate post-operative analgesia with good patient satisfaction has been observed with this technique. Objective: To assess the duration of postoperative analgesia and complications in patients receiving epidural anaesthesia with Morphine, Midazolam and Pethidine in combination with Bupivacaine. Methods: We prospectively studied 75 patients who were scheduled for elective lower limb orthopaedic surgery with epidural anaesthesia at Lumbini Medical College, Palpa from 2010 March to 2012 March. They were randomly divided by lottery method into three equal groups. Group ‘A’ (BP) received 50 mg epidural Pethidine (3 ml) with 13 ml of 0.5% Bupivacaine. Group ‘B’ (BM) received 5 mg (3 ml) epidural Morphine with 13 ml of 0.5% Bupivacaine and Group ‘C’ (BMM) received 5 mg (1 ml) epidural Morphine with 13 ml 0.5% Bupivacaine and 2 mg (2 ml) epidural Midazolam. All the patients were observed for 24 hours for quality of analgesia and other side effects like nausea, vomiting and pruritus. Data were analysed by Statistical Package for Social Sciences (SPSS-16) software. Results: The result of the study shows the duration of analgesia was prolonged in BM group than BP group and even more so in BMM group (p value <0.001). Incidence of nausea and vomiting in BMM group was lower than in BP and BM group but statistically the difference was not significant (p value: 0.489). Pruritus was absent in BP group, less in BMM group while significantly higher in BM group. Conclusion: The use of epidural Morphine and Midazolam in combination with Bupivacaine is the satisfactory method of post operative analgesia. When Midazolam is added, duration of analgesia can be increased with decrease in incidence of nausea, vomiting and pruritus. Journal of Kathmandu Medical College Vol. 2, No. 3, Issue 5, Jul.-Sep., 2013 Page: 117-121 DOI: http://dx.doi.org/10.3126/jkmc.v2i3.9961 Uploaded date : 3/4/2014